First household survey on drug abuse in São Paulo, Brazil, 1999: principal findings - Galduróz, José Carlos Fernandes; Noto, Ana Regina; Nappo, Solange Aparecida; Carlini, Elisaldo Luiz de Araújo (São Paulo Medical Journal, 2003)
CONTEXT: In order to establish prevention programs regarding psychotropic drug use that are adapted to specific populations it is, first of all, important to have data on the realities of such consumption. Single data points are not enough for drawing up a profile of society in relation to drugs. OBJECTIVE: The aim of this household survey was to determine the incidence of illegal drug, alcohol, tobacco and psychotropic medication use, and thus the number of persons dependent on drugs, alcohol and nicotine, and to evaluate their perception regarding how easy it is to obtain psychotropic drugs. TYPE OF STUDY: Epidemiological survey. SETTING: All of the 24 cities in the State of Sao Paulo with more 200,000 inhabitants participated in the study. METHOD: The sampling was constructed from weighted probabilistic stratified conglomerates obtained via two-stage selection. In each municipality sampled, census sectors (generally 200- 300 households) were first selected. Then, households and a respondent were selected to provide information from his/her point of view. The SAMHSA questionnaire (Substance Abuse and Mental Health Services Administration) of the U.S. Department of Public Health was used, after translation and adaptation to Brazilian conditions. RESULTS: A total of 2,411 persons aged 12-65 years old were interviewed, of whom 39.9% weremen. Lifetime use of any psychotropic drug other than alcohol and tobacco was 11.6%: much less than in the U.S. (34.8%). The alcohol dependence rate was 6%, similar to findings from other countries. Marijuana was the illegal drug most cited as used daily (6.6%): a prevalence much lower than in the U.S. (32.0%). Inhalant use was next in frequency of use (2.7%): about 10 times less than in the United Kingdom (20%). Cocaine use (2.1%) was about 5 times less than in the U.S. (10.6%). There was no report of heroin use, although there was a surprisingly high perception regarding the ease of obtaining heroin: 38.3% said it was easy to obtain. CONCLUSION: This study supports the implementation of better prevention programs regarding drug abuse in São Paulo state.